Burglars on the job streetlife and residential break-ins - Wright, Richard T.; Decker, Scott H. 1950- (Northeastern Univ. Pr., 1994)
Drawing on extensive interviews with 105 active burglars in St. Louis, Missouri, Burglars on the Job presents offenders' perspectives on the process of burglarizing a residence. The authors, Richard T. Wright and Scott H. Decker, consider motivations for the decision to burglarize a dwelling, explore how and why the burglar selects targets, examine how the offender executes the break-in, discuss strategies for searching a residence, and detail the ways in which the burglar disposes of stolen goods. Unlike earlier studies of residential burglary, which collected data from a small number of offenders within a prison environment, this ground-breaking work examines a larger sample of unincarcerated burglars, all identified and contacted without the assistance of criminal justice agencies or authorities. As a result, Wright and Decker were able to obtain more honest and forthright responses from the offenders, and they were able to study the burglars' decision-making processes within the context of streetlife culture. The authors found the offenders' needs to support activities such as drinking and drug-taking often shape the decision to commit a residential break-in, and that burglars rarely consider risks or the threat of sanctions. Burglars on the Job concludes with an insightful discussion that considers the implications of the authors' findings for theories on criminal decision-making, crime prevention policy, and field research.
Keywords: Delicten; Inbrekers; Burglars -- Missouri -- Saint Louis; Burglary -- Missouri -- Saint Louis